A Model for Public Policies Instability Based on Grounded Theory Approach - Mansour Usefirad; Abbas Nargesian (فرایند مدیریت و توسعه, 2024)
Purpose: The present article intended to reach a paradigmatic model which can show the instability of public policies in the private sector. Methodology: To identify the main components of the model, related questions were developed based on the literature. Semi-structured interviews were performed with 33 experts from the private sector and in-depth interviews ,too, were performed with a number of specialists from the relevant department. Participant were selected according to both  purposeful and theoretical sampling methods. Findings: Grounded theory approach together with the procedure put forward by Corbin and Strouss were used for data analysis. Through open, selective and central coding; components of paradigmatic model based on instability of poblic policies and causal factors; moderating variables; mediating variables; and strategies, we could finally reach the outcomes and the paradigmatic model of instability in public policies for the private sector, which are now are  presented. Originality: Regarding the type and the nature of this research, as well as the comprehensiveness of the dimentions studied, the most noticeable and the most recent factors of instability of public policies for the private sector (in the industrial domain) brought about the findings of the research. Based on the opinions of the experts, one can utilize the acquired results to expand the vision and knowledge of poliy making in the production area.